Losses by volatilization of 15 N-urea and 15N-ammonium sulphate from a calcareous soil of the central coastal region of Peru - Urquiaga, Segundo; Victoria, Reynaldo L.; Buitrón, Fausto; Neyra, Jorge Chávez (Pesquisa Agropecuaria Brasileira, 2014)
A study was performed in greenhouse to investigate the volatilization losses on nitrogen from 15N labelled urea (10.191 atom % 15N) and ammonium sulphate (7.801 atom % 15N) applied to pots of a calcareous soil (Entisol) from the central coastal region of Peru. The pots contained 1.5 kg of soil and were planted with four maize plants. The labelled N was added at a rate of 150 μg N.g-1 soil at 15 days after emergence (DAE) of the maize. The N fertilizer were applied in four different ways: on the surface of the dry soil, on the surface of the wetted soil, on the surface of the dry soil but immediately irrigated, or buried at a depth of 4cm in wetted soil. The losses of fertilizer N, by volatilization were calculated from a mass balance of the applied labelled N at the end of the experiment (45 DAE). It was found that: a) a greater proportion of the N from urea (65%) was taken up by the plant than that provided by ammonium sulphate (52%) and fertilizer use efficiency was greater when the fertilizers were applied to the surface of the dry soil or buried in wetted soil; b) the urea left more residual N in the soil but there were no significant differences between the addition methods; c) the loss of N from ammonium sulphate 39%), by volatilization, was greater than that from urea (23,6%); d) the losses of fertilizer N applied to the surface of the wetted soil (42%) or from that applied to dry soil which was immediately irrigated (37%) were significantly greater than when the fertilizer was applied to the surface of dry soil (23,4%) or buried in wet soil (22%).
Keywords: nitrogen sources; nitrogen application methods; nitrogen recovery by plant; nitrogen balance.